DAMPAK BEBAN KERJA, STRES KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI HONORER - Suhaila Rasya; Bagus Handoko; Ezzah Nahrisah (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This study aims to determine the effect of compensation, organizational climate and work environment simultaneously on employee performance at Badan Pertanahan Nasional Kota Medan. The total population in this study was 102 people, and by using the saturated sampling technique, a sample of 102 people was obtained. The analysis technique used is multiple linear regression. The results showed that compensation has a significant effect on employee performance at Badan Pertanahan Nasional Kota Medan. Organizational climate has a significant effect on employee performance at Badan Pertanahan Nasional Kota Medan. The work environment has a significant effect on employee performance at Badan Pertanahan Nasional Kota Medan. Compensation, organizational climate and work environment have a significant effect on employee performance at Badan Pertanahan Nasional Kota Medan.